The Ring-Shaped Antenna Modelling and Diffraction Measurements Modulator - Jankauskas, Z.; Laurinavicius, L. (Elektronika ir Elektrotechnika, 2001)
The experimental measurements of direction diagram and angle of diffraction of the ring-shaped antenna is very complicated and expensive procedure. If the antenna is placed in ionosphere (satellites, aircraft) the measurements are completely impossible. In such cases it is convenient to use antenna modelling by the help of helicon beams in solid state plasma. Helicon waves will propagate in metals and semiconductors when a magnetic field is applied. They have an exact analogy with whistler wave which is propagating in the rarefied plasma of the Earth’s ionosphere. It means that the properties of ionosphere can be duplicated in magnetized semiconductors.Gaussian electromagnetic beams in magnetized solid state plasma provide the possibility for modelling the ring-shaped antenna with the dimensions much smaller (~ 20 times) than the real object. Experimental arrangement is considered. The direction diagram and angle of diffraction in this case may be measured in laboratory instead of field works.